2015
DOI: 10.1371/journal.pone.0120189
|View full text |Cite
|
Sign up to set email alerts
|

Worse Breast Cancer Prognosis of BRCA1/BRCA2 Mutation Carriers: What's the Evidence? A Systematic Review with Meta-Analysis

Abstract: ObjectiveConflicting conclusions have been published regarding breast cancer survival of BRCA1/2 mutation carriers. Here we provide an evidence-based systematic literature review.MethodsEligible publications were observational studies assessing the survival of breast cancer patients carrying a BRCA1/2 mutation compared to non-carriers or the general breast cancer population. We performed meta-analyses and best-evidence syntheses for survival outcomes taking into account study quality assessed by selection bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 64 publications
5
62
0
3
Order By: Relevance
“…Mutations in BRCA are more commonly studied in the setting of breast or ovarian cancer. 22,23 Although the association between BRCA mutations and PDAC in both the familial and seemingly sporadic case is known, the rarity of the diagnosis compounded by the infrequent nature of genetic testing has led to few studies of BRCA mutation and its impact on patient survival. 2428 In theory, BRCA mutations in PDAC may fall within the unstable genotype, representing a more mutagenic and aggressive tumor biology and subsequent worse survival.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in BRCA are more commonly studied in the setting of breast or ovarian cancer. 22,23 Although the association between BRCA mutations and PDAC in both the familial and seemingly sporadic case is known, the rarity of the diagnosis compounded by the infrequent nature of genetic testing has led to few studies of BRCA mutation and its impact on patient survival. 2428 In theory, BRCA mutations in PDAC may fall within the unstable genotype, representing a more mutagenic and aggressive tumor biology and subsequent worse survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, to reduce the potential influence of this group, women younger than 49 years were excluded. A systematic review has also shown that there is no difference in the proportions of advanced stage cancers between carriers and noncarriers of the BRCA1/2 mutation . Another issue is that participation in the screening program was voluntary, which meant that several factors may have influenced attendance; in particular, it is known that women with a low SES have lower attendance rates .…”
Section: Discussionmentioning
confidence: 99%
“…(c) that found that of 66 studies assessing the survival of BRCA1/2 mutation carriers, only 8 corrected for confounding by adjuvant treatment [32]. Current evidence suggests that contrary to currently held beliefs, if confounding by treatment is taken into account, differences in survival between BRCA1/2 mutation carriers and sporadic breast cancer patients if any are likely to be small.…”
Section: Discussionmentioning
confidence: 95%